2016
DOI: 10.1007/s00894-016-2946-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of position and number of methoxy group(s) to tune the nonlinear optical properties of chalcone derivatives: a dual substitution strategy

Abstract: Using the state-of-art computational techniques, we limelight a structure-property relationship for the position and number of methoxy group(s) to tune the optical and nonlinear optical (NLO) properties (first hyperpolarizability) of chalcone derivatives. Based on our previously synthesized chalcones [system 1 ((E)-1-(2,5-dimethylthiophen-3-yl)-3-(2-methoxyphenyl)prop-2-en-1-one and system 4 (E)-1-(2,5-dimethylthiophen-3-yl)-3-(2,4,5-trimethoxyphenyl)prop-2-en-1-one)], we systematically design several novel de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Similar compounds tend to change their NLO response magnitude with the position of the substituents on the phenyl ring. Such an effect was previously studied and confirmed elsewhere [46,47]. In those studies, the methoxy group influenced the NLO response when placed in different positions (para, ortho, and meta) of the phenyl ring, achieving the highest response when placed in the para-position of the phenyl ring.…”
Section: First Molecular Hyperpolarizabilitysupporting
confidence: 69%
“…Similar compounds tend to change their NLO response magnitude with the position of the substituents on the phenyl ring. Such an effect was previously studied and confirmed elsewhere [46,47]. In those studies, the methoxy group influenced the NLO response when placed in different positions (para, ortho, and meta) of the phenyl ring, achieving the highest response when placed in the para-position of the phenyl ring.…”
Section: First Molecular Hyperpolarizabilitysupporting
confidence: 69%
“…Over the past some years, several investigations have been performed on routine push-pull chromophores to explore their potential for optical and nonlinear optical properties. 32,33 Unlike the previous investigations, in present study, we chose the N-doped graphene that has already well-characterized structure.…”
Section: Introductionmentioning
confidence: 99%
“…The first‐order hyperpolarizability (β) value for 6 is 208.14 is 325.22 folds higher than urea (0.64 x10 −30 esu, at B3LYP/6‐31G (d) level of theory) and the second‐order hyperpolarizability (γ) for 6 is 3028.93 is 2704.40 folds higher than urea (1.12 x 10 −36 esu, at B3LYP/6‐31G (d) basis set) ( Supplementary information Table S6 ). Moreover, the β and γ values of these compounds were compared with the reported donor‐π‐acceptor coumarin‐chalcones and their BF 2 complexed dyes, we found that β values of these dyes are lower and γ values are higher than the reported donor‐π‐acceptor coumarin‐chalcones and their BF 2 complexed dyes and also the β and γ values of these compounds were compared with the reported chalcone derivatives and found that the β and γ values of synthesized compounds are found to higher than the reported chalcone derivatives ( Supplementary information Table S7 ). The CAM−B3LYP functionals work better for calculations, which has 19–65% HF exchange percentage compared to 20%, 50% for B3LYP and BHHLYP respectively .…”
Section: Resultsmentioning
confidence: 71%